Pornography Use Could Lead to Addiction and Was Associated With Reproductive Hormone Levels and Semen Quality: A Report From the MARHCS Study in China - Cui, Zhihong; Mo, Min; Chen, Qing; Wang, Xiaogang; Yang, Huan; Zhou, Niya; Sun, Lei; Liu, Jinyi; Ao, Lin; Cao, Jia (Frontiers in Endocrinology, 2021)
This study aimed to investigate the situations of pornography use among male college students of China, to explore the addiction possibility for pornography use, and to study the associations between pornography use and reproductive hormone levels and semen quality. 568 participants met the inclusion criteria and finished all of the questionnaires and hormone level and semen parameter examinations. A majority of participants (except one) had pornography use experience, 94.2% participants started pornography use before college, and 95.9% participants reported they had masturbation experience when using pornography. Early contact to pornography, frequent pornography use, high amount of time spending on pornography use, and frequent masturbation during pornography use were correlated with addiction trends. Earlier pornography use was found to be associated with lower serum PRL(prolactin), FSH (follicle-stimulating hormone) and Prog(progesterone) as well as lower sperm concentration and total sperm count. Higher frequent of pornography use was associated with lower serum E2(estrogen). In conclusion, pornography use was common among male college students in China. Early contact, high frequent use, and high frequent of masturbation during pornography use could lead to addiction trends and aberrant reproductive hormone levels and semen quality.